MOOCs and academic libraries: a chance or a problem? An overview - Laura Testoni (JLIS.it, 2013)
Massive open online courses(MOOCs) are online courses free and open to anyone: the MOOCs enrollement is essentially unlimited. Purpose of this essay is to offer an overview on the debate about the development of the MOOCs and about their impact on academic libraries information services. In the first part MOOCs are examined as an emerging educational tool and a very "disruptive" innovation in the field of the higher education. The development of MOOCs platforms as Coursera, EdX and Udacity in 2012 starts an enthusiastic phase (the so-called "peak of inflated expectations" in the Hype cycle model), followed by a wide debate in the educational / academic milieu. We consider the strengths and the critical points of MOOCs. In the second part the author focuses the attention on the interaction between the MOOCs and the academic libraries. The following issues are taken into account: the involvement / the roles of the librarians in the implementation of the MOOCs; the copyright management in the MOOCs environment; the information literacy; the library advocacy; the impact of the MOOCs on information services provided by academic libraries.